Upaya Peningkatan Dukungan Keluarga Dalam Menjaga Diit Pasien Gout Athritis - Rendra Putra, Eryan, Vinami Yulian, S.Kep, Ns., M.Sc (2016)
Gout arthritis ( Uric Acid-Urate) is a gross result of body's metabolism that normaly come from protein digestion that shall be dumped in kidney, Sweat or Feses. There is some pain condition that the patient would suffer from uric acid in late night or when they wake up from their sleep in the morning. A patient of uric acid should maintain their breakfast protein, there is a lot of families that still didn't know what is uric acid, one of the families support on develop and maintain their families health is aware of their diit in order to minimize or seize the pain resulted by Uric Acid. Objectives on this research is about how to raise a family support on maintaining a patient diit from Uric Acid. It use descriptive method with finding an brief interpreted fact and collecting data as real as possible. After 5 clinical act (60 minutes/1 meeting), A family and patient that have such a disorder would know about what is uric acid and how to vanished the uric acid pain and also how to maintain their diit (Protein) In nursing activity there is an importance of family's support protect and maintain the patient health, After all the medication act, We know that patient's family can understand how to protect the uric acid and aid them from it disease, In this case, Family's support is important in order run their healthy life and aid the patient from the Uric Acid.